Hubungan lnteraksi Sosial Anggota Kelompok Tani dengan Partisipasi Petani dalam Kegiatan Penyuluhan Pertanian di Kecamatan Banua Lawas Kabupaten Tabalong - Saidi Saidi; Mariani Mariani; Eka Radiah (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
The social interaction is useful in observing and studying the various problems in the community . By applying a participatory approach , it allows the community to identify their own problems andempower themselves to overcome the problems. The study determine the level of social interaction among members of farmer groups, the level of farmer participation in extension activities , and the correlation between two factors in Kecamatan Banua Lawas, Tabalong. The study finds that the level of social interaction, which include social contact and communication, and the level of farmer participation in extension activities are in the medium category . Both factors also have significant correlation.